Consequences of military actions for aquatic ecosystems and fisheries of Ukraine. Thematic web-bibliography - Ir. Hrytsynyak; T. Shvets (Ribogospodarsʹka Nauka Ukraïni)
Purpose. Numerous facts of the harmful impact of military actions caused by the military aggression of the Russian Federation on the environment of Ukraine were recorded and documented by many Ukrainian and foreign scientists and other specialists. The purpose of this work was to form a reference list of publications on the impact of war on water resources and hydrobionts, as well as the aquaculture industry of Ukraine in general and fisheries in particular.